Studi Teologi-Etis Hubungan Perilaku Korupsi Sebagai Salah Satu Dampak Sikap Hidup Hedonis - Yosefo Gule (UIN Sunan Kalijaga Yogyakarta, 2021)
In this paper, the author will conduct a theological-ethical study of the relationship between corrupt behavior as one of the impacts of a hedonic attitude to life. The research method in writing this article is to use a descriptive qualitative study method with a library research approach. The practice of corruption is one of the impacts of a hedonic life attitude in humans who prioritizes the desires of the flesh rather than the desires of the spirit, cannot fulfill what is on them, so that humans become greedy, arrogant and evil and this is against God's will and is also not in line with God's mission is to bring peace on earth as it is in heaven. If this desire for corruption cannot be controlled in humans, then corruption seems to be a natural act that is no longer seen as a crime. Self-transcendence is very important to be used as an effort of human praxis to go beyond its hedonistic sides, and to allow itself to be guided by the noble values of life that come from religious teachings and from the context of the community in life.